The digital economy and crypto-currencies: challenge or threat to traditional society - L. Zvyagin (State University of Management, 2019)
Currently, information technologies are not standing still, they are in constant change, starting from previous innovations, adjusting not only to market trends, but also the changing economic environment in which they live. A key factor in the development andgrowth of both the world and the economy of our state in modern realities is the digital economy. It determines the national security and independence of the country, the competitiveness of the players, the country’s place on the world stage. The aim of this articleis to make an attempt to understand the prospects of application of information technologies of the digital economy and to study the ways of their use in the programming environment related directly to the economic situation. It is important to identify the roleand benefts of technology in the digital economy.Blockchain technology takes its origin in the emergence of cryptocurrency-bitcoin, which serves as an alternative payment system, which in turn, unlike traditional payment systems is not controlled by any state or banks. A distinctive feature of this system is thatthe addition and storage of data is carried out within the network of nodes, and takes the form of a linear chain, there is no need to involve a Central Supervisory authority in such conditions. Only network users can add new transactions. Thus, for the digitaleconomy, the blockchain system is a distributed database consisting of separate blocks taking the form of an unbroken chain that stores both all the transactions that took place and all the data of wallets that once existed.it is an “eternal digital magazine” thatcan be programmed to register almost anything that represents a certain value. This explains the fact that not only cryptocurrency fnds its application in the blockchain system. Each cell of the blockchain includes a timestamp and a link to the previous block.Because of what it can be virtually infnite, but in real life the possibilities of technology limit it.As an advanced technology, the blockchain model, various types of cryptocurrencies, in particular bitcoin, as well as the issues of mathematical foundations of the digitalization process, system archetypes and the formation of the framework model have beenconsidered.